Uji Aktivitas Antibakteri Ekstrak Etanol Daun Gaharu (Aquilaria microcarpa Baill.) Terhadap Bakteri Staphylococcus aureus dan Proteus mirabilis - Sari, Rafika; Muhani, Mutiara; Fajriaty, Inarah (Pharmaceutical Sciences and Research, 2017)
Leaves agarwood (Aquilaria microcarpa Bail) is one of the natural materials that can be used as an antibacterial. This study aims to determine the content type of secondary metabolites and antibacterial activity against Staphylococcus aureus and Proteus mirabilis by the method of Kirby-Bauer disc diffusion. Simplicia leaves agarwood macerated with ethanol 96%. Results of phytochemical screening of ethanol extract of leaves agarwood contain flavonoids, phenols, tannins, saponins and steroids. Furthermore, the TLC for the assertion of their chemical compounds in extracts of leaves agarwood using a mobile phase of butanol: acetic acid: water (4: 1: 5) with the stationary phase silica gel GF254 with spotting FeCl3 5% for phenolic and AlCl3 5% for flavonoids later in UV detection at 254nm and 366nm. Control positive used is siprofloksasin 50 μg while control negative used is DMSO 20 % . Based on the results of the average diameter zone obstruent extract ethanol leaves agarwood in staphylococcus aureus by concentration of the 300 mg / ml, 400 mg / ml, 500 mg / ml is 12.50 mm, 13,51 mm, 15,80 mm. while in proteus mirabilis by concentration of the 300 mg / ml, 400 mg / ml, 500 mg / ml is 12,10 mm, 13,26 mm, 15.19 mm. This shows that extracts ethanol leaves agarwood having activity on Gram positive and Gram negative.